Formulasi Body Scrub dari VCO (Virgin Coconut Oil) dan Serbuk Daun Jeruk Purut (Citrus hystrix): Formulation of Body Scrub with VCO (Virgin Coconut Oil) and Kaffir Lime Leaf (Citrus hystrix) Powder - Widyasanti, Asri; Azara, Widya Nugrahani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2024)
Body scrub is a skin care product that functions to remove dead skin cells so that the skin becomes smoother and brighter. The purpose of this research is to make a body scrub formulation with VCO (virgin coconut oil) and variations in concentration of kaffir lime leaf powder, and test the body scrub according to SNI 16-4399-1996. The method used includes product testing to ensure compliance with SNI standards. The results showed that the formulation with virgin coconut oil and 2% concentration of kaffir lime leaf powder was the most optimal. Product testing showed that the body scrub met the SNI standard.